Comparison of Microbial Communities in the Sediments and Water Columns of Frozen Cryoconite Holes in the McMurdo Dry Valleys, Antarctica - Sommers, Pacifica; Darcy, John L.; Porazinska, Dorota L.; Gendron, Eli M. S.; Fountain, Andrew G.; Zamora, Felix; Vincent, Kim; Cawley, Kaelin M.; Solon, Adam J.; Vimercati, Lara; Ryder, Jenna; Schmidt, Steven K. (Frontiers in Microbiology, 2019)
Although cryoconite holes, sediment-filled melt holes on glacier surfaces, appear small and homogenous, their microbial inhabitants may be spatially partitioned. This partitioning could be particularly important for maintaining biodiversity in holes that remain isolated for many years, such as in Antarctica. We hypothesized that cryoconite holes with greater species richness and biomass should exhibit greater partitioning between the sediments and water, promoting greater biodiversity through spatial niche partitioning. We tested this hypothesis by sampling frozen cryoconite holes along a gradient of biomass and biodiversity in the Taylor Valley, Antarctica, where ice-lidded cryoconite holes are a ubiquitous feature of glaciers. We extracted DNA and chlorophyll a from the sediments and water of these samples to describe biodiversity and quantify proxies for biomass. Contrary to our expectation, we found that cryoconite holes with greater richness and biomass showed less partitioning of phylotypes by the sediments versus the water, perhaps indicating that the probability of sediment microbes being mixed into the water is higher from richer sediments. Another explanation may be that organisms from the water were compressed by freezing down to the sediment layer, leaving primarily relic DNA of dead cells to be detected higher in the frozen water. Further evidence of this explanation is that the dominant sequences unique to the water organisms that do not live in cryoconite holes or the Dry Valleys (e.g. vertebrates) as their closest sequence matches, and which could represent unknown microbial animals or DNA from atmospheric deposition of dead biomass in the low biomass water. Although we cannot rule out spatial niche partitioning occurring at finer scales or in melted cryoconite holes, we found no evidence of partitioning between the sediments and water in frozen holes. Future work should include more sampling of cryoconite holes at a finer spatial scale, and characterizing the communities of the sediments and water when cryoconite holes are melted and active.